2009
DOI: 10.1007/s12011-009-8340-y
|View full text |Cite
|
Sign up to set email alerts
|

Selenium, Lead, and Cadmium Levels in Renal Failure Patients in China

Abstract: Whole blood and serum samples of Chinese stable chronic renal failure (CRF) patients (n = 81), hemodialysis patients (n = 135), posttransplant patients (n = 60), and subjects with normal renal function (NRF; N = 42) were collected, as well as water and dialysate samples from five dialysis centers. The concentration of selenium (Se), lead (Pb), and cadmium (Cd) was measured by atomic absorption spectrometry. The mean serum Se levels in patients with different degrees of renal failure were significantly lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 28 publications
6
19
0
1
Order By: Relevance
“…In this study, mean serum selenium levels were significantly lower in HPs than in healthy controls (Table 1) as also reported by others [5][6][7][23][24][25][26][27]. In contrast, a study of the influence of glucose in the dialysate on oxidative stress intensity, glutathione activity, and plasma Se in HPs [5] found plasma Se concentrations to be increased by hemodialysis.…”
Section: Resultssupporting
confidence: 87%
“…In this study, mean serum selenium levels were significantly lower in HPs than in healthy controls (Table 1) as also reported by others [5][6][7][23][24][25][26][27]. In contrast, a study of the influence of glucose in the dialysate on oxidative stress intensity, glutathione activity, and plasma Se in HPs [5] found plasma Se concentrations to be increased by hemodialysis.…”
Section: Resultssupporting
confidence: 87%
“…Thus, Bing Chen et al, found a positive correlation between the blood cadmium levels and the time on dialysis. Such observations were also been reported by Skarupskiene et al, [33,34]. Sharupskiene et al had also reported elevated blood cadmium levels in haemodialysis patients [34].…”
Section: Resultssupporting
confidence: 80%
“…D Van Renterghem et al, had demonstrated elevated concentrations of cadmium in the sera of five patients who were on haemodiafiltration [31]. Bing Chen et al, who studied the whole blood and serum samples of stable Chinese chronic renal failure patients (n=81), haemodialysis patients (n=135), posttransplant patients (n=60) and subjects with normal renal functions (n=42), found a high prevalence of elevated cadmium levels in the haemodialysis patients [33]. The blood cadmium level in the haemodialysis patients was also significantly higher as compared to that in the subjects with stable chronic renal failure (p<0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Bing Chen et al, who studied the whole blood and the serum samples of Chinese stable chronic renal failure patients, haemodialysis patients, post-transplant patients and subjects with normal renal functions, found a low prevalence of the elevated lead levels (>200 µg/L) in the dialysis patients, which was similar to the findings of Su-Hui Lee et al, [9,10]. Ja-Liang Lin et al, studied the blood lead levels in 315 patients who were on chronic peritoneal dialysis in an 18-month prospective study.…”
Section: Discussionsupporting
confidence: 58%